Phytochemistry of isolated essential oils from Cautleya spicata (Sm.) Baker for their pesticidal evaluation and in-silico approaches to reveal the mode of nematicidal action - Sonu Kumar Mahawer; Manar Fawzi Bani Mfarrej; Ravendra Kumar; Himani Karakoti; Om Prakash; Satya Kumar; Dharmendra Singh Rawat; Aditi Kundu; Pieter Malan; Faheem Ahmad (Cogent Food & Agriculture)
This study aimed to assess the chemical composition and pesticidal activities of essential oils (EOs) from Cautleya spicata rhizomes and aerial parts. The EOs were assessed against root-knot nematodes (Meloidogyne incognita) by mortality and hatchability bioassays and the phytotoxicity of the EOs was determined against Raphanus raphanistrum subspp. Sativus (radish) and Cichorium intybus (chicory) seeds. In-silico screening of the primary constituents of EOs and five chosen target proteins of the nematode was conducted to predict the expected mechanism of action of these oils. p-Cymene and β-pinene were the key compounds in the EOs from the rhizomes and aerial parts. The EO from the aerial parts (LC50 value = 0.555 µL/mL for nematode mortality assay and IC50 value = 0.016 µL/mL for nematode egg hatchability after 96 h) exhibited significantly higher nematicidal activity than the rhizome EO. However, rhizome EO showed higher phytotoxic activity against radish (R. raphanistrum) with lower IC50 values (0.157 and 0.123 µL/mL for RLI and SLI, respectively) and chicory (C. intybus) seeds (100% inhibition at 1.0 µL/mL concentration). Docking studies revealed the strongest inhibitory actions of β-selinene against acetylcholinesterase (AChE) and cytochrome c oxidase (CytC), spathulenol against glutathione S-transferase (GST-1), and β-eudesmol against heat shock protein 90 (HSP90) and odorant response gene-3 (ODR3) proteins. The study unveiled the chemical diversity present in both the EOs and rhizomes of C. spicata along with their considerable potential as plant-based pesticidal agents effective against nematodes and weed species.